2017
DOI: 10.1159/000477203
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Pepsinogen I and beta Helicobacter pylori Infection Are Risk Factors for Aspirin-Induced Gastroduodenal Injury

Abstract: Background: Whether gastric hyperchlorhydria and Helicobacter pylori infection contribute to aspirin-induced gastroduodenal injury still lacks evidence. Because serum pepsinogens (PGs) and gastrin-17 (G17) can reflect gastric acid secretion, this study intended to elucidate whether serum PGs, serum G17, and H. pylori infection are associated with aspirin-induced gastrointestinal injury. Summary: A total of 60 patients taking low-dose aspirin for more than 1 month were enrolled in this study. Serum PG I, PG II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…In fact, many studies have defined the thresholds of serum PGs based on the characteristics of the data [24,33,34]. It has been reported that the cutoff value of PGI was 123 ng/mL in the aspirin-induced gastroduodenal injury [24]. This threshold was similar to the one acquired in our experimental results (PGI Z 131 ng/mL).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In fact, many studies have defined the thresholds of serum PGs based on the characteristics of the data [24,33,34]. It has been reported that the cutoff value of PGI was 123 ng/mL in the aspirin-induced gastroduodenal injury [24]. This threshold was similar to the one acquired in our experimental results (PGI Z 131 ng/mL).…”
Section: Discussionsupporting
confidence: 83%
“…Further, demographic, lifestyle, lipids, renal function and inflammatory indicators were adjusted in the Model 2, and Model 3 (Table 2), the correlation between PGI/PGR has been slightly weakened. The concentrations of serum PGs can also be affected by the usage of nonsteroidal anti-inflammatory drugs (NSAIDs) through inducing GMI [24,25]. Aspirin, one of the most commonlyused NSAIDs, can cause digestive bleeding, perforation, and ulceration, by disrupting the gastric epithelial cell barrier and systematically inhibiting gastric mucosal protection [25e30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar association between a decreased PG I/II ratio and precancerous gastric conditions was also confirmed in several European countries, although the authors criticized the PG low specificity and its testing limitation for assessing gastric cancer risks [ 114 ]. Moreover, the measurement of PG I levels in the serum and the assessment of H. pylori infection may also be used to identify patients at high-risk for gastroduodenal injury induced by aspirin [ 115 ]. Interestingly, a cutoff value of PG I ≤ 31.2 ng/mL and PG I/II ratio ≤ 4.6 was able to discriminate for a past H. pylori infection in patients with Group A blood in a multicenter study [ 116 ].…”
Section: Non-invasive Testsmentioning
confidence: 99%
“…vs 61.7% and 39.2% for CRP. Among these biomarkers, Shan et al demonstrated that combination of increased serum PG 1 level and presence of H. pylori infection, in the group of patients taking aspirin, can indicate aspirininduced gastrointestinal damages 34. …”
mentioning
confidence: 99%